Media Referensi Berbasis Teknologi Facebook Bagi Wartawan dalam Menyusun Berita - Lian Agustina Setiyaningsih; Muhammad Hanif Fahmi; Fitrataqwin Sawidodo (LPPM Stikosa - AWS, 2020)
Facebook has various functions including helping professional activities. As a social media used by 140 million Indonesians, Facebook has a significant role in helping journalists work. The phenomenon of using social media references is also widely practiced abroad. However, the convergence of the media questions the limitations of using Facebook by journalists in compiling news. This is because the convergence of media provides flexibility for social media users to be both communicators and communicators in it. This study used a qualitative narrative method which interviewed 9 informants for print, electronic and online journalists. The narrative method describes the practice of using Facebook media sources from the eyes of journalists who are used as sources in presenting news. Purposive sampling is a technique of taking the number of informants. The result of this research is that Facebook is used as a reference media by journalists in finding, managing and compiling news. Limitation on the use of references is in the activity of finding news objects and strengthening news writing data. There are two features on Facebook that are used as references, namely updates and groups. Journalists act as gatekeepers in distributing messages. Steps taken in managing news information on Facebook include: checking, filtering, crosschecking and writing news. Meanwhile, the criteria for information accessed are the weight of information with social impacts, proximity, the tendency of the media regarding news content, content uniqueness, extraordinary, high value and news.